Análise da cultura de segurança em um hospital de ensino da região centro-oeste do Brasil - Tobias, Gabriela Camargo (2013)
In the context of health, the safety culture centered on the quality of care and the systematization of work processes contributes to human error prevention avoidable and, therefore, for the patient safety. The study aims to analyze the perception of a teaching hospital nurses about the dimensions of safety culture’s patient. The methodology is descriptive, exploratory, carried out at a teaching hospital in the Central West region of Brazil, with a population of 117 nurses. The data were collected in October to December of 2011 through autoaplicavel instruments,those belongs to the Hospital Survey on Patient Safety Culture, proposed and used by Agency for Health Research and Quality, specific for the detection of safety culture in hospital, translated and validated for the portuguese language. The data were analysed by the Statistical Package for Social Sciences Program, version 18.0. The project was approved, protocol 064/2008. The percentual of participants were 84.8 % of the nurses of the hospital, 89.7 % were female, predominant age range between 45 to 51 years, 51% with 16 to 21 years of profession, 36% with the same time in the institution and 13.7 % worked in the Emergency Room. The weekly workload of 87% was about 20 to 39 hours and 96% had directly contact with the patient. The reply “Not punitive to mistakes” had the lowest rate, 28%. The weaknesses for the institution were: the team considers that their mistakes could be used against them; the team was afraid that the mistakes were recorded in their functional files; insufficient staff; they work more than necessary; occurrence of problems in the exchange of information between the units; the security has to be sacrificed instaed of doing more things; patient safety problem in the unit, procedures and inadequate systems for the mistakes prevention. The strength points were: the supervisor/manager takes the suggestions to improve the patient safety, considers security problems; work actively doing things to improve the servisse quality; support each other; work in a team; treating with respect and having a good relationship with professionals from other units. However, 59% considered safety patient acceptablevin the unit, and 52% said they never reported adverse events. The conclusion was that the research gave the nurses perception and envolved them with the patient security, the same as how to prove that the aplication of a analysed instrument for actions can be used for estimulating the adoption of politics those bring changes and attitudes for the development of institution security culture.